ANALISIS PENGARUH TINGKAT PENGANGGURAN TERBUKA (TPT) TERHADAP TINGKAT KEMISKINAN DI JAWA TENGAH:PENDEKATAN KUANTITATIF DENGAN MENGGUNAKAN DATA BADAN PUSAT STATISTIK TAHUN 2020–2022 - Hapsari Larasati; Bambang Agus Herlambang, Ahmad Khoirul Anam (CV. ADIBA AISHA AMIRA, 2024)
This research aims to analyze the influence of the Open Unemployment Rate (TPT) on the poverty levels in the province of Central Java, utilizing a quantitative approach and the Geographic Information System (GIS) method. The data employed in this study are sourced from the Central Bureau of Statistics (BPS) for the years 2020–2022. The analytical method incorporates a quantitative approach to measure the relationship between the open unemployment rate and poverty levels in Central Java. Additionally, the Geographic Information System (GIS) method will be employed to map the spatial distribution o.f unemployment and poverty rates in the region. The integration of these two methods is anticipated to provide a more comprehensive understanding of the impact of unemployment on poverty levels, aiding in the formulation of more precise and targeted policy decisions. The anticipated results of the analysis include the identification of patterns and relationships between the open unemployment rate and poverty levels in each district/city in Central Java. Consequently, this research is expected to contribute to a deeper understanding of employment and poverty issues at the regional level, providing a foundation for the development of more effective policies to address these challenges